Reseña de Bybee, J. and S. Fleischman (1995), Modality in Grammar and Discourse, (TypologicalStudies in Language 32), Amsterdam/Philadelphia, John Benjamins Publishing Company. - José Luis Berbeira Gardón (Pragmalingüística)
Se trata de una reseña de Bybee, J. and S. Fleischman (1995), Modality in Grammar and Discourse, (TypologicalStudies in Language 32), Amsterdam/Philadelphia, John Benjamins Publishing Company.